PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Risambessy, Agusthina (Fakultas Ekonomi, UIN Maliki Malang, 2017)
Abstract: This study aims to analyze and explain the effects of compensation and work environment onemployee performance at the Office of District Salahutu Central Maluku District. Research in the Office ofKecamatan Salahutu, Central Maluku District. The population of this research is all employees of DistrictOffice of Salahutu Regency of Central Maluku which need 57 sampling technique by using census samplingdata. Data completion method used in this research is through questionnaire distribution to employees whobecome sample. Comprehensive data was analyzed by using multiple regression analysis method to measurethe magnitude of influence or influence of independent variable to dependent variable, either partial orsimultaneous influence with other independent variables. The result of the research shows that there issignificant influence on employee performance. Thus all the hypotheses in the research received